A parametric study on oil film pressure measurements in a single piston-ring configuration. (April 2013) - Dellis, Polychronis; Arcoumanis, Constantine
Oil film pressure, the driving force behind piston-ring lubrication phenomena, is measured in a single piston-ring simulating rig after the successful installation of a miniature pressure transducer. The partition of overall load-carrying capacity between direct surface interaction and hydrodynamic action is clearly of some significance if the characteristics of the piston seal are to be understood and predicted with any confidence. It is therefore important that the contribution of the fluid film lubrication to load support be adequately represented. This study presents an extensive load, speed, temperature and piston-ring curvature parametric study on how the measured pressure profile at mid-stroke is affected in terms of peak pressure, magnitude and shift in the trailing edge of the piston ring, taking into account cavitation appearance and lubricant viscosity variation.